Effect of acupuncture combined with antidepressants on post-stroke depression: A network meta-analysis of nine acupuncture therapy - Li, Chun; Chen, Shasha; Liu, Shuang; Mu, Yang; Su, Mouxiao (Frontiers in Neurology, 2023)
Background Post-stroke depression (PSD) is a common psychiatric complication of mental disorders after stroke. Acupuncture for PSD is effective and has few adverse effects. As a classical complementary and alternative therapy, acupuncture is often used in combination with antidepressants for PSD. However, there is a wide variety of acupuncture therapies, and the efficacy of different acupuncture varies. In this study, a network meta-analysis (NMA) was used to assess the clinical efficacy of different acupuncture combined with antidepressants for the treatment of PSD. Methods A comprehensive search of PubMed, The Cochrane Library, EMbase, Web of Science, CNKI, CBM, VIP, and Wan-Fang databases for published randomized controlled trials of acupuncture combined with antidepressants for the treatment of PSD was conducted. The time frame for the literature search was from the date of database creation to April 30, 2022. The Cochrane risk of bias tool for randomized trials (RoB 2.0) was used to evaluate the bias risk of the included studies. Data analysis was performed by STATA 14.0 software. Results A total of 38 literatures with 2,898 patients involving nine acupuncture therapies were included. NMA results were as follows: moxibustion plus antidepressants had the best efficacy in terms of improving total effective rate. Conventional acupuncture plus antidepressants was the most effective in improving HAMD scores. In terms of improving SDS scores, acupressure plus antidepressants was the most effective. In terms of improving NIHSS scores, moxibustion plus antidepressants showed the best results. Conclusion A comparison of the efficacy indicators of the nine different acupuncture therapies combined showed that moxibustion plus antidepressants, conventional acupuncture plus antidepressants and acupressure plus antidepressants were superior in the treatment of PSD. Based on the shortcomings of the existing studies, this conclusion needs to be validated by additional high-quality randomized controlled trials.